The role of moral emotions and individual differences in consumer responses to corporate green and non-green actions - Xie, Chunyan; Bagozzi, Richard P.; Grønhaug, Kjell (Journal of the Academy of Marketing Science, 2015)
We investigate the mediating role of moral emotions and their contingency on individual characteristics in consumer responses to corporate green and non-green actions. Two between subjects experiments were conducted to test our hypotheses on samples of adult consumers. The results show that, for corporate non-green actions, various individual difference characteristics (social justice values, empathy, moral identity, self-concept) moderate the elicitation of negative moral emotions (contempt, anger, disgust), which, in turn, lead to consumer negative responses (negative word of mouth, complaint behaviors, boycotting). Moreover, for corporate green actions, empathy moderates elicitation of positive emotions on gratitude, which, in turn, influences consumer positive responses (positive word of mouth, resistance to negative information, identification with the company, investment). This study adds to extant research by examining understudied “hot” moral emotional processes underlying consumer reactions toward corporate environmental responsibility and irresponsibility. Implications for marketing communication and segmentation decisions are considered.